SUPERBOOK: CERITA FIRMAN TUHAN KREATIF BAGI ANAK SEKOLAH MINGGU - Aser Lasfeto; Delaya Saron Hariadi; Etminor Riwu; Gabriela Eldad (Bethel Press, 2021)
The stories told by Sunday school were rated as having decreased in terms of creativity. This is because we see so many new generations entering the world of Sunday school. The obstacles experienced by parents increase as increased busyness requires time for children to understand God's word. This article aims to examine more deeply the existence of superbooks as a tool for providing creative and exciting words of God. The method used is descriptive qualitative literature study. Then the researchers found a result where the superbook provided interesting programs of God's word starting from digital memorized verses and God's word with interesting and exciting animations. This brought children's emotions to see that the stories of God's word were presented maturely and beautifully.